Current trends in carbon emission trading: Theoretical perspectives, research methods and emerging themes - Xiaoping, Zhang; Syuhada Jasni, Nur; Fadhilah Ismail, Rina (Edelweiss Applied Science and Technology, 2024)
Since the inception of the EU carbon emissions trading market, it has experienced substantial growth. However, there is a shortage of comprehensive analysis on the policy implications of carbon emissions trading in the context of the low-carbon economy. The article utilizes bibliometric and content analytic methodologies to thoroughly examine the features and content of 116 relevant pieces of literature. Based on this analysis, a research model on the carbon emissions trading schemes is constructed. The study findings indicate a significant surge in the quantity of published material since 2021, with a predominant focus on terms related to the low carbon economy, such as environmental regulation and carbon emission. The research hotspots are related to transformation and upgrading and enterprise performance, etc. The research theory involves compliance cost theory, Porter’s hypothesis theory, emissions trading theory and green innovation theory, empirical research is the main method of carbon emissions trading research. Emerging theme analyses are summarized in terms of the economic, environmental, technological and social effects of carbon trading. Finally, there are research conclusions and future research trends.